Manajemen Sumber Daya Manusia Pendidikan di Era Digital (Studi Kesiapan Guru dalam Pembelajaran Berbasis Teknologi) - Syaiful Bahri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze human resource management in education in the digital era, focusing on teacher readiness to implement technology-based learning. The research method used was a systematic literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. This approach involved formulating research questions, searching for relevant literature, and qualitatively analyzing and synthesizing previous research findings. The results indicate that teacher readiness for technology-based learning remains suboptimal, characterized by limited digital literacy, low utilization of interactive learning platforms and artificial intelligence-based technology, and the continued dominance of conventional learning methods. Key inhibiting factors include limited technological infrastructure, lack of ongoing training, resistance to change, and suboptimal school policies supporting digital transformation. The study's conclusions emphasize that improving teacher readiness for technology-based learning requires planned human resource management in education through ongoing professional training, the provision of adequate facilities and infrastructure, and institutional policy support that encourages innovation and the integration of technology into the learning process. Keywords: Human Resource Management, Teacher Readiness, Digital Learning, Educational Technology, Digital Literacy